2008
DOI: 10.1016/j.nurt.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Modulation of γ-Secretase for Alzheimer's Disease

Abstract: Summary:The 4-kDa amyloid ␤-peptide (A␤) is strongly implicated the pathogenesis of Alzheimer's disease (AD), and this peptide is cut out of the amyloid ␤-protein precursor (APP) by the sequential action of ␤-and ␥-secretases. ␥-Secretase is a membrane-embedded protease complex that cleaves the transmembrane region of APP to produce A␤, and this protease is a top target for developing AD therapeutics. A number of inhibitors of the ␥-secretase complex have been identified, including peptidomimetics that block t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 75 publications
3
111
1
2
Order By: Relevance
“…Perhaps most promisingly, there exists an extensive drug-discovery repositioning opportunity for potential SPP inhibitors in existing chemical libraries from pharmaceutical companies. PS and SPPs are part of the A22-family integral membrane aspartyl proteases; it is therefore likely that there exist numerous potent PfSPP drug-like inhibitors in PS-directed chemical libraries, reducing cost barriers for development (39)(40)(41). Indeed, LY-411575 was a product of previous a PS drug-discovery effort.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most promisingly, there exists an extensive drug-discovery repositioning opportunity for potential SPP inhibitors in existing chemical libraries from pharmaceutical companies. PS and SPPs are part of the A22-family integral membrane aspartyl proteases; it is therefore likely that there exist numerous potent PfSPP drug-like inhibitors in PS-directed chemical libraries, reducing cost barriers for development (39)(40)(41). Indeed, LY-411575 was a product of previous a PS drug-discovery effort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that A␤ levels in brains can be reduced by decreasing ␥-secretase activity (reviewed in Ref. 41). Therefore, an exact understanding of the mechanism by which cellular ␥-secretase activity is negatively regulated might provide the basis for a novel therapeutic strategy for AD other than development of direct inhibitors of ␥-secretase.…”
Section: Discussionmentioning
confidence: 99%
“…While there are currently no drugs in clinical use that target these mechanisms, many putative disease-modifying inhibitors are under active development and some have shown in vivo efficacy in mouse models and in clinical trials. [4][5][6][7][8] One of the most notable examples is Neurochem's Alzhemed (tramiprosate) that was developed to prevent amyloid formation and deposition in the brain, and thus modify the course of AD. Unfortunately, despite Alzhemed's promise in Phase II clinical trials, the recent U.S.…”
Section: Introductionmentioning
confidence: 99%